2008
DOI: 10.1080/03768350802090709
|View full text |Cite
|
Sign up to set email alerts
|

The struggle for the streets: processes of exclusion and inclusion of street traders in Durban, South Africa

Abstract: Millions of people worldwide make a living selling goods on the streets. This article traces the ebbs and flows of exclusion and inclusion of street traders from Durban's public spaces from the 1920s to the present. It shows that over time the city has, variously, expelled traders, allowed unmanaged trading and actively incorporated traders into urban plans. It suggests that there is an ongoing struggle for access to the streets, and draws attention to the role of the national and local state, as well as local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 10 publications
1
72
1
Order By: Relevance
“…The findings in a study by Holness et al (1999) showed that 75 per cent of the responded hawkers were women. Their dominance is one of the socio-economic factors in a hawking business (Cummins & Harvey, 1996;Mitullah, 2003;Agnello & Moller, 2004;Manganga, 2007;Motala, 2008;Skinner, 2008). This study somehow does not agree with similar studies conducted in other parts of the world.…”
Section: Independent Variablescontrasting
confidence: 56%
See 2 more Smart Citations
“…The findings in a study by Holness et al (1999) showed that 75 per cent of the responded hawkers were women. Their dominance is one of the socio-economic factors in a hawking business (Cummins & Harvey, 1996;Mitullah, 2003;Agnello & Moller, 2004;Manganga, 2007;Motala, 2008;Skinner, 2008). This study somehow does not agree with similar studies conducted in other parts of the world.…”
Section: Independent Variablescontrasting
confidence: 56%
“…Hawkers with high income per month are the ones who are likely to have bigger selling markets and who are mostly mobile and they often sell to other hawkers. The findings in a study by Skinner (2008) were that fruit and vegetable hawkers in South Africa earn between R300 and R600 per month, and an average turnover of R1000 per month. Tissington's (2009) findings from his study were that hawkers earned between R800 to R1600 a month depending, according to them, on the weather.…”
Section: Independent Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…These demonstrations may take the form of public rallies, where vendors sometimes march on city authorities and hand over demands and grievances, an approach which has been used effectively by vendors in Durban, South Africa, in preventing eviction (Skinner, 2008b) as well as in Caloocan in Manila, the Philippines (Recio & Gomez, 2013). Sometimes these public demonstrations take violent forms, as has been reported in Mexico City in Mexico (Crossa, 2009).…”
mentioning
confidence: 99%
“…They sell handicrafts, ice cream, lottery tickets, and just about everything else. But South Africa is different [8]. In cities like Johannesburg, Cape Town, and Durban, street vending is entirely absent or confined to a very restricted area.…”
Section: Women In Informal Employment: Globalizing and Organizing (Wimentioning
confidence: 99%